P064 INTERFERON-GAMMA INDUCED VASCULAR IMPAIRMENT CONTRIBUTES TO THE PATHOGENESIS OF INFLAMMATORY BOWEL DISEASES. (18th January 2018) - Langer, Victoria; Britzen-Laurent, Nathalie; Regensburger, Daniela; Naschberger, Elisabeth; Stürzl, Michael; Winkler, Thomas; Waldner, Maximilian; Schmid, Benjamin; Tripal, Philipp; Lee, Somin; Jeon, Noo Li; Wohlfahrt, Thomas; et al.
Abstract: Background: Inflammatory Bowel Diseases (IBD) are characterized by upregulation of Interferon-gamma (IFN-γ). Recently we showed that IFN-γ blockade by a specific antibody in Dextran Sodium Sulfate (DSS)-colitis mouse model results in increased angiogenesis and reduced vessel permeability(1). The aim of the present project was to validate the specific contribution of vascular effects of IFN-γ to the pathogenesis of IBD. Methods: For examination of vascular IFN-γ effects in vivo, we established an endothelial cell-specific Ifngr2-knock-out (Ifngr2 ΔEndoC ) mouse model. Vessel sprouting after IFN-γ stimulation of metatarsals was used for functional validation of the knock out. In order to analyze the specific contribution of vascular effects of IFN-γ to the pathogenesis of IBD, Ifngr2 ΔEndoC and control mice were subjected to DSS-colitis. Angiogenesis and vascular barrier function of the colon were compared. Results: Comparison of metatarsal angiogenic sprouting from Ifngr2 ΔEndoC and control mice showed that endothelial-specific knock-out of Ifngr2 abrogates the angiostatic effects of IFN-γ. Induction of DSS-colitis revealed that Ifngr2 ΔEndoC mice, compared to control mice, had a reduced inflammation of the colon. Investigation of specific vascular alterations showed an increased angiogenesis rate for Ifngr2 ΔEndoC mice accompanied by an improved vascular barrier function, marked by higher vascular pericyte coverage and reduced vessel permeability. Conclusions: Our results indicate for first time an important pathofunction of the blood vessels in IBD. Specifically an IFN-γ-induced disruption of the vascular barrier function exaggerated the course of disease. This may open new therapy options. 1. Haep et al. Interferon Gamma Counteracts the Angiogenic Switch and Induces Vascular Permeability in Dextran Sulfate Sodium Colitis in Mice. Inflamm Bowel Dis. 2015.